Economic activities and CO2 emissions: Evaluating the impacts of renewable energy, industrial growth, and financial development in CO2-intensive economies - Ben Jebli, Mehdi; Dallali, Atef (Center of Biomass & Renewable Energy (CBIORE), 2025)
This study addresses the pressing challenge of mitigating carbon dioxide (CO2) emissions within the top ten emitting countries, which are critical to achieving global climate goals yet often analyzed separately. We investigate the intricate relationships between economic growth (GDP), renewable and non-renewable energy consumption (RE, NRE), financial development (FDI), industrial value-added (IVA), and CO2 emissions from 1990 to 2021, overcoming the limitations of single-country studies and mixed findings in existing literature. Employing a panel-based Pooled Mean Group-Autoregressive Distributed Lag (PMG-ARDL) model and Granger causality tests, we disentangle short-run and long-run dynamics, revealing that non-renewable energy significantly increases emissions while renewable energy, financial development, and industrial value-added offer mitigating effects. We provide nuanced evidence supporting the Environmental Kuznets Curve (EKC) hypothesis, suggesting a potential pathway toward sustainable growth. Furthermore, Granger causality analysis reveals significant bidirectional relationships, highlighting the interconnectedness of economic and environmental factors. We translate these findings into actionable policy recommendations, emphasizing targeted investments in clean technologies and financial strategies to foster industrial development while simultaneously curbing emissions. By providing a comprehensive analysis of these dynamics within a key group of countries, this research offers critical insights for overcoming the challenges of emissions reduction and achieving sustainable development.